2005
DOI: 10.1128/jcm.43.8.4037-4040.2005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Streptococcus pneumoniae Antigen in Bronchoalveolar Lavage Fluid Samples by a Rapid Immunochromatographic Membrane Assay

Abstract: Streptococcus pneumoniae prevails as a leading cause of community-acquired pneumonia (CAP), and it ranks as one of the organisms most commonly involved as the cause of severe CAP requiring intensive care admission (1, 9). Recently, an immunochromatographic membrane test (ICT) for rapid detection of S. pneumoniae antigen (NOW Streptococcus pneumoniae test; Binax, Portland, Maine) has been marketed. Till now, the test has been validated for urine and cerebrospinal fluid samples only. According to the package lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
0
8
0
2
Order By: Relevance
“…However, studies have been performed on nasopharyngeal secretions (10), middle ear effusions (11), cerebrospinal fluids (36), bronchoalveolar lavage fluids (17), pleural fluids (30), and blood cultures (29). The present study included the first three of these sample types, and the test was further successfully adapted to bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies have been performed on nasopharyngeal secretions (10), middle ear effusions (11), cerebrospinal fluids (36), bronchoalveolar lavage fluids (17), pleural fluids (30), and blood cultures (29). The present study included the first three of these sample types, and the test was further successfully adapted to bone tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Performing the pneumococcal antigen test on BAL is reported to have a sensitivity of 54–95% and a specificity of 86.8–100% for pneumococcal pneumonia 215 216. When available, use of PCR on BAL has been shown to be useful in the detection of legionella,217 218 with reported sensitivity and specificity approaching 100% 218.…”
Section: Sampling and Diagnostic Accuracymentioning
confidence: 99%
“…Moreover, risk of contamination from the upper airways has also been reported with this method. Some studies have indicated promising results regarding immune-chromatographic membrane test for S. pneumoniae applied on BAL (Jacobs et al 2005). Bronchoscopy has mostly been used in the intensive care of patients treated with mechanical ventilation.…”
Section: Culture Of Bronchoalveolar Lavage and Protected Specimen Brushmentioning
confidence: 99%